Foxp2 regulates neuronal differentiation and neuronal subtype specification. Issue 7 (18th February 2014) - Chiu, Yi‐Chi; Li, Ming‐Yang; Liu, Yuan‐Hsuan; Ding, Jing‐Ya; Yu, Jenn‐Yah; Wang, Tsu‐Wei
ABSTRACT Mutations of the transcription factor FOXP2 in humans cause a severe speech and language disorder. Disruption of Foxp2 in songbirds or mice also leads to deficits in song learning or ultrasonic vocalization, respectively. These data suggest that Foxp2 plays important roles in the developing nervous system. However, the mechanism of Foxp2 in regulating neural development remains elusive. In the current study, we found that Foxp2 increased neuronal differentiation without affecting cell proliferation and cell survival in primary neural progenitors from embryonic forebrains. Foxp2 induced the expression of platelet‐derived growth factor receptor α, which mediated the neurognic effect of Foxp2. In addition, Foxp2 positively regulated the differentiation of medium spiny neurons derived from the lateral ganglionic eminence and negatively regulated the formation of interneurons derived from dorsal medial ganglionic eminence by interacting with the Sonic hedgehog pathway. Taken together, our results suggest that Foxp2 regulates multiple aspects of neuronal development in the embryonic forebrain. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 74: 723–738, 2014